Manajemen Strategi Pemasaran Pendidikan di SD Ma’arif NU Klirong - Aminudin, Fuad; Muthoharoh, Ngaliyatun; Hafid, Seafi Nur; Chasanah, Silmi Muhimatul; Mahmudah, Siti; El-Hasani, Yunan; Isnaeni, Zulakhoh; Sukataman, Sukatamam (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2023)
This research aims to describe the planning, implementation and evaluation of educational marketing management at SD Ma'arif NU Klirong. This research approach is qualitative, using observation, interviews and documentation methods. The data analysis technique used is an interactive model and data triangulation to check the validity of the data. Several approaches used in efforts to strengthen education marketing are the formation of a PPDB committee, the extended family approach, establishing collaboration with kindergartens, collaborating with mass media to attract public interest and online publications. Improving the quality of schools is supported by the existence of various superior and extracurricular programs to meet the needs of society in keeping up with increasingly advanced developments. Another supporting factor is that this school is able to provide confidence and comfort in terms of facilities and from a religious perspective, apart from that, the elementary school also acts as a TPQ for students so that it can be known to the wider community and the inhibiting factor is in terms of completeness of facilities.